The Political Economy of Road Safety: Case Study of Bogotá (2018)
Between 1996 and 2006, the city of Bogota reduced its traffic fatality rate by over 60% due to a combination of policies, programs and processes between key actors. Since then the city has maintained a stable rate over time. Bogota is well-known for the implementation of the bus rapid transit (BRT) system known as Transmilenio but few studies have examined the influence on road safety outcomes of this mass transit investment in combination with other policies and programs from a political economy perspective. This paper developed a mixed methods approach to examine the influence of BRT investments on road safety and identify the factors that explain the significant reduction in traffic fatalities over time. A spatial hot spot analysis combined with a generalized ordered logit model found a strong influence of infrastructure provision on reducing the probability of traffic fatalities along the BRT corridors for specific years. A qualitative data analysis based on 12 semi-structured interviews with key stakeholders identified three main themes explaining this significant reduction: education and behavior, infrastructure and sustainable mobility and enforcement and safety. Programs and projects on these three themes and an institutional reform of the local government, in addition to the continuity of policies among city mayors over time, also explain the significant reduction. The analysis shows that given a favorable political context, important improvements in road safety can be achieved in short time, even if the main objective is public security or enhanced mobility through sustainable modes.